SSA challenge program: Lake kivu pilot learning site : Overview. Meeting objectives and expectations - Nyamwaro, Sospeter S.; Buruchara, Robin Arani (International Center for Tropical Agriculture, 2010)
Overview, Meeting Objectives and Expectations Presented at the Cross-Site Regional Review & Writeshop Meeting of LKPLS, November 08-12, 2010, Kigali, Rwanda